2016
DOI: 10.1016/j.stemcr.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Roles of Canonical and Noncanonical Wnt Signaling in Human Embryonic Cardiomyocyte Development

Abstract: SummaryWnt signaling is a key regulator of vertebrate heart development; however, specific roles for human cardiomyocyte development remain uncertain. Here we use human embryonic stem cells (hESCs) to analyze systematically in human cardiomyocyte development the expression of endogenous Wnt signaling components, monitor pathway activity, and dissect stage-specific requirements for canonical and noncanonical Wnt signaling mechanisms using small-molecule inhibitors. Our analysis suggests that WNT3 and WNT8A, via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 63 publications
7
81
1
3
Order By: Relevance
“…Among the major pathways enriched in the P3 poorly preserved modules, we found that 27 out of 58 Wnt-related genes were regulated in a chamber-specific manner, including components from the canonical and noncanonical signaling pathways (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Remarkably, established inhibitors of canonical β-catenindependent signaling (Wif1, Dkk3, and Sost1) were upregulated in RVs compared with LVs, while several members of the noncanonical Wnt11 signaling (Wnt11, Wnt5a, Ror2, Sfrp5, and Rock2) were enriched in RVs.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Among the major pathways enriched in the P3 poorly preserved modules, we found that 27 out of 58 Wnt-related genes were regulated in a chamber-specific manner, including components from the canonical and noncanonical signaling pathways (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Remarkably, established inhibitors of canonical β-catenindependent signaling (Wif1, Dkk3, and Sost1) were upregulated in RVs compared with LVs, while several members of the noncanonical Wnt11 signaling (Wnt11, Wnt5a, Ror2, Sfrp5, and Rock2) were enriched in RVs.…”
Section: Resultsmentioning
confidence: 97%
“…Among the different developmental signals (21)(22)(23), Wnt signaling pathways play prominent roles in cardiac precursor's commitment, cell proliferation, differentiation, and fate (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).Actions by the Wnt family molecules can be classified into the canonical Wnt/β-catenin-dependent pathway and the noncanonical pathway, which is generally β-catenin independent, and its function can be mediated by 2 distinct modules of the noncanonical signaling: (a) the planar cell polarity (PCP) pathway; and (b) the Wnt/ Ca 2+ pathway, which involves calmodulin-dependent kinase II (CamKII), protein kinase C (PKC), and calcineurin. These factors may coordinate important cellular signaling processes including regulating the expression of key cell cycle regulators.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…B.1, C.1, C.2a e C.2b) têm como alvo FZD4 e GSK3, da via WNT, e BMPR, ACVR, receptores de Nodal, da via TGFβ, e assim, propõe-se que o mecanismo de promoção de pluripotência por estes miRNAs se dê pela inativação de sinais de diferenciação por WNT, como a ativação de FZD4 na geração de cardiomiótitos (MAZZOTTA et al, 2016), e por TGFβ, como no efeito pró-diferenciação das BMPs (RICHTER et al, 2014), permitindo somente uma regulação positiva destas vias sobre a pluripotência. Um exemplo prático desta hipótese de mecanismo é a participação do miR-181 na reprogramação por meio da ativação de WNT, levando ao acúmulo de β-catenina nuclear, e inibição da sinalização de TGFβ .…”
Section: Mirnas Induzem Diferenciação Celular Ou Pluripotência Por Mounclassified